TCR-like bispecific antibodies toward eliminating infected hepatocytes in HBV mouse models - Yang Shi; Zihan Wang; Jingjing Xu; Wenxia Niu; Yubin Wu; Huiyu Guo; Jinmiao Shi; Zonglin Li; Baorong Fu; Yunda Hong; Zikang Wang; Wenjie Guo; et al. (Emerging Microbes and Infections)
Therapeutics for eradicating hepatitis B virus (HBV) infection are still limited and current nucleos(t)ide analogs (NAs) and interferon are effective in controlling viral replication and improving liver health, but they cannot completely eradicate the hepatitis B virus and only a very small number of patients are cured of it. The TCR-like antibodies recognizing viral peptides presented on human leukocyte antigens (HLA) provide possible tools for targeting and eliminating HBV-infected hepatocytes. Here, we generated three TCR-like antibodies targeting three different HLA-A2.1-presented peptides derived from HBV core and surface proteins. Bispecific antibodies (BsAbs) were developed by fuzing variable fragments of these TCR-like mAbs with an anti-CD3ϵ antibody. Our data demonstrate that the BsAbs could act as T cell engagers, effectively redirecting and activating T cells to target HBV-infected hepatocytes in vitro and in vivo. In HBV-persistent mice expressing human HLA-A2.1, two infusions of BsAbs induced marked and sustained suppression in serum HBsAg levels and also reduced the numbers of HBV-positive hepatocytes. These findings highlighted the therapeutic potential of TCR-like BsAbs as a new strategy to cure hepatitis B.